Chemical assessment of eleven Cinnamon aromatic water populations from Fars (Iran) local markets in comparison to a standard sample - Bita Shahpar; Mahmoodreza Moein; Mohammad M. Zarshenas (Shiraz University of Medical Sciences, 2016)
Current study aimed to chemically assess volatile constituents of eleven commercial cinnamon hydrosols purchased from Fars province (Iran) local markets in comparison to a standard sample. Via a liquid extractor, the volatile oil fractions of samples and also the standard hydrosol yielded from essential oil extraction of an authenticated cinnamon bark sample were recovered. Gas chromatography/ flame ionization detector (GC/FID) and subsequently GC/MS (GC/mass spectroscopy) were employed to assess and identify the chemical compositions of prepared samples. The procedure of analysis revealed in the appearance of totally 25 components. Cinnamaldehyde was found as the main constituent in ten populations (S2-S11) as well as in the standard sample (63.04-91.61%). Considerable amounts of Dibutyl phthalate, as a commonly used plasticizer was also detected in all samples. This is the first report of analysis and identification of volatile constituent in cinnamon hydrosol, a common medicinal beverage. Although, high amount of Cinnamaldehyde in cinnamon hydrosol can introduce this tasty medicinal beverage for further studies similar to the respective botanical part or various usual extracts, more comprehensive monitoring is to be performed on safety, purity and quality of such preparation.